Density and Tensile Properties Analysis of Biocomposite from Lid Film Waste and Oil Palm Empty Fruit Bunch Fiber - Salman Farishi; Siti Mutia Mawaddah; Mochamad Chalid; Agustino Zulys; Muhammad Ghozali (Jurnal Sains Materi Indonesia, 2026)
Multilayer plastic waste, particularly from the bottled water industry, represents a persistent challenge in current plastic waste management strategies. Simultaneously, oil palm empty fruit bunch (OPEFB) waste, though often discarded, possesses significant potential for sustainable material development. This study explores the utilization of both waste streams as raw materials for biocomposite fabrication, thereby addressing environmental concerns while reducing dependence on virgin polymer resources. The multilayer lid film waste (comprising PET, LDPE, and LLDPE) and OPEFB fibers were processed through crushing, sieving, and extrusion to form pellets with varying OPEFB fiber loadings (30%, 50%, and 70% by weight). The resulting biocomposite was characterized using FTIR, XRD, SEM, density measurements, and tensile testing. The biocomposite containing 70% OPEFB exhibited the slowest degradation but also the lowest crystallinity (10.84%). In contrast, the 30% OPEFB composite showed the highest tensile strength (16.86 MPa) and elongation at break (3.23 MPa). SEM analysis revealed that a higher fiber content increased the porosity within the composite matrix. These findings demonstrate the potential of combining multilayer plastic and OPEFB waste for biocomposite applications, contributing to both material innovation and environmental sustainability.